Prospective technical validation and assessment of intra-tumour heterogeneity of a low density array hypoxia gene profile in head and neck squamous cell carcinoma. - Betts, G; Eustace, A; Patiar, S; Valentine, H; Irlam, J; Ramachandran, A; Merve, A; Homer, J; Möller-Levet, C; Buffa, F; Hall, G; Miller, C; et al. (2013)
BACKGROUND AND PURPOSE: Tumour hypoxia is associated with a poor prognosis in head and neck squamous cell carcinoma (HNSCC), however there is no accepted method for assessing hypoxia clinically. We aimed to conduct a technical validation of a hypoxia gene expression signature using the TaqMan Low Density Array (TLDA) platform to investigate if this approach reliably identified hypoxic tumours. MATERIALS AND METHODS: Tumour samples (n=201) from 80 HNSCC patients were collected prospectively from two centres. Fifty-three patients received pimonidazole prior to surgery. TaqMan Low Density Array-Hypoxia Scores (TLDA-HS) were obtained by quantitative real-time PCR (qPCR) using a 25-gene signature and customised TLDA cards. Assay performance was assessed as coefficient of variation (CoV). RESULTS: The assay was sensitive with linear reaction efficiencies across a 4 log(10) range of inputted cDNA (0.001-10 ng/μl). Intra- (CoV=6.9%) and inter- (CoV=2.0%) assay reproducibility were excellent. Intra-tumour heterogeneity was lower for TLDA-HS (23.2%) than for pimonidazole (67.2%) or single gene measurements of CA9 (62.2%), VEGFA (45.0%) or HIG2 (39.4%). TLDA-HS in HNSCC cell lines increased with decreasing pO(2). TLDA-HS correlated with Affymetrix U133 Plus 2.0 microarray HS (p<0.01) and positive pimonidazole scores (p=0.005). CONCLUSIONS: Gene expression measurements of hypoxia using a 25-gene signature and TLDA cards are sensitive, reproducible and associated with lower intra-tumour heterogeneity than assaying individual genes or pimonidazole binding. The approach is suitable for further assessment of prognostic and predictive capability in clinical trial material.